2022
DOI: 10.1002/pen.26010
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy resin matrix integrating epoxy‐polydimethylsiloxane based self‐healing microcapsules: Healing efficiency, mechanical and thermal stability

Abstract: Environmental factors such as climate change, temperature fluctuations, and mechanical forces hinder long-term space, transportation, and research missions due to structural damage. We report an innovative system to overcome this problem. The self-healing structure under examination is an epoxy as a polymeric matrix, which includes microcapsules embedded with epoxypolydimethylsiloxane (PDMS), as a healing agent, separately combined by microcapsules embedded with triethylenetetramine (TETA) as a hardener or cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) were utilized to examine the composition of the encapsulated therapeutic agent and their self-healing capabilities. 128 The aviation industry usages neat polymer only in limited components and therefore real benefit of selfhealing materials is possible only if promising results are seen in composites. The present state of research shows promising abilities to develop composites with good mechanical properties and adequate self-healing utilizing multimode self-healing technologies.…”
Section: Aviation Grade Composites and Emerging Soft Materials With B...mentioning
confidence: 99%
See 1 more Smart Citation
“…Differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) were utilized to examine the composition of the encapsulated therapeutic agent and their self-healing capabilities. 128 The aviation industry usages neat polymer only in limited components and therefore real benefit of selfhealing materials is possible only if promising results are seen in composites. The present state of research shows promising abilities to develop composites with good mechanical properties and adequate self-healing utilizing multimode self-healing technologies.…”
Section: Aviation Grade Composites and Emerging Soft Materials With B...mentioning
confidence: 99%
“…Microcapsules containing epoxy‐PDMS were polymerized via in situ polymerization in this study: (1) formation of the PUF and (2) encapsulation of epoxy‐PDMS. Differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) were utilized to examine the composition of the encapsulated therapeutic agent and their self‐healing capabilities 128 …”
Section: Aviation Grade Composites and Emerging Soft Materials With B...mentioning
confidence: 99%
“…One of the characteristics of polymer materials significant for their application in structures operating at elevated temperatures is their thermal and thermal oxidative stability. [33][34][35][36][37][38] The most common method of thermal and thermal oxidative stability evaluation is non-isothermal TGA method corresponding to short-term stability 37,[39][40][41] but there are not a lot of works concerning long-term isothermal oxidative stability of phthalonitrile resins. 38,[42][43][44] The reported results of TGA studies revealed a valuable data related to the products of phthalonitriles degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resin (EP) is a widely used and indispensable thermosetting plastic for modern industry because of its excellent moldability, thermal, mechanical, anti-corrosion, and chemical resistant properties. [1][2][3] However, as a brittle polymer with three dimensions crosslinked structure inside, it lacks self-lubricating properties for being used in friction and wears protection. [4][5][6] To improve the lubricating and anti-wear properties of traditional epoxy resin, researchers have made great efforts, such as mixing lubricating secondary polymer (polytetrafluoroethylene (PTFE), [7,8] rubber, [9] polyurethane (PU) [10] ), incorporating anti-wear fillers (fibers [11][12][13] and inorganic particles [14,15] ) and doping nanofillers (nanosheets, [6,16,17] nanotubes [18,19] and nanoparticles [5,20] ) with both functions.…”
Section: Introductionmentioning
confidence: 99%